2012
DOI: 10.1088/0031-9155/57/17/5543
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative x-ray detection system for gold nanoparticle tumour biomarkers

Abstract: X-ray fluorescence techniques have proven beneficial for identifying and quantifying trace elements in biological tissues. A novel approach is being developed that employs x-ray fluorescence with an aim to locate heavy nanoparticles, such as gold, which are embedded into tissues. Such nanoparticles can be functionalized to act as markers for tumour characteristics to map the disease state, with the future aim of imaging them to inform cancer therapy regimes. The uptake of functionalized nanoparticles by cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 18 publications
(22 reference statements)
1
42
0
Order By: Relevance
“…This study has demonstrated the capability of the system to image GNP distribution and to distinguish between GNP concentrations. There is a strong potential that this technique can be extended to quantitative imaging, as this system has already demonstrated ability for quantitative measurement to within ± 0.005 mgAu ml −1 at low concentrations (between the detection limit of 0.001 mgAu ml −1 and 0.1 mgAu ml −1 ) (Ricketts et al 2012). Figures 7 and 8 also demonstrate that both XRF imaging systems can be used to image GNP concentrations as low as 0.025 mgAu ml −1 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study has demonstrated the capability of the system to image GNP distribution and to distinguish between GNP concentrations. There is a strong potential that this technique can be extended to quantitative imaging, as this system has already demonstrated ability for quantitative measurement to within ± 0.005 mgAu ml −1 at low concentrations (between the detection limit of 0.001 mgAu ml −1 and 0.1 mgAu ml −1 ) (Ricketts et al 2012). Figures 7 and 8 also demonstrate that both XRF imaging systems can be used to image GNP concentrations as low as 0.025 mgAu ml −1 .…”
Section: Discussionmentioning
confidence: 99%
“…Lower concentrations were not tested in this study due to restrictions on acquisition time at the synchrotron source. However it can be inferred from previous detection limit measurements that the step and shoot system may be sensitive to even lower concentrations (Ricketts et al 2012). The addition of polycapillary optic technology will impact on the achievable sensitivity and detection limit in the following ways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19] Monochromatic beams produced with synchrotron sources are known to give higher contrast for K-shell XRF signal than clinical polychromatic x-ray sources. 20 A quasimonochromatic x-ray beam obtained from proper conversion of a clinical polychromatic x-ray beam will help to improve the current detection limit of platinum drugs by shifting Compton scattering peaks (background noise) away from the signals of interest, i.e., the K-shell platinum XRF peaks, in the acquired energy spectrum. 19,21,22 Imaging time could be a major concern in the current design using a first-generation CT geometry because the beams are acquired sequentially.…”
Section: Resultsmentioning
confidence: 99%
“…Energy-dispersive X-ray fluorescence (ED-XRF) has become a measurement technique widely applied to many fields such as medicine, environment, geology and cultural heritage [1][2][3][4][5]. Nowadays, both laboratory and in-field XRF apparatus are operated daily, and handheld instruments are extensively used.…”
Section: Introductionmentioning
confidence: 99%